2022
DOI: 10.3389/fgene.2022.831206
|View full text |Cite
|
Sign up to set email alerts
|

Increasing Taxa Sampling Provides New Insights on the Phylogenetic Relationship Between Eriobotrya and Rhaphiolepis

Abstract: Eriobotrya (Rosaceae) is an economically important genus with around 30 species. It is widely distributed in tropical and warm temperate regions of Asia, with most of its species in China, Myanmar, and Vietnam. However, Eriobotrya is often confused with the smaller genus Rhaphiolepis, and the phylogenetic relationships between the two genera are controversial. Here we present phylogenetic analyses of 38 newly generated Eriobotrya and Rhaphiolepis nrDNA together with 16 sequences of nrDNA and 28 sequences of IT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 52 publications
0
4
0
Order By: Relevance
“…Many studies have attempted to resolve the relationships within Araliaceae using molecular markers of ITS or plastid-region data, but the relationship of Araliaceae was still unclear [ 1 – 3 , 5 , 7 9 , 11 ]. In addition, studies show that increased sampling of taxa can greatly improve overall phylogenetic accuracy [ 56 58 ]. Our study and Valcárcel et al [ 14 ] had found that using the whole plastomes, with an appropriate sampling, can greatly aid the relationship between the deep pedigrees of the Araliaceae.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have attempted to resolve the relationships within Araliaceae using molecular markers of ITS or plastid-region data, but the relationship of Araliaceae was still unclear [ 1 – 3 , 5 , 7 9 , 11 ]. In addition, studies show that increased sampling of taxa can greatly improve overall phylogenetic accuracy [ 56 58 ]. Our study and Valcárcel et al [ 14 ] had found that using the whole plastomes, with an appropriate sampling, can greatly aid the relationship between the deep pedigrees of the Araliaceae.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, differences in biparental and maternal inheritance could have caused the divergent results of the ITS and cpDNA evolutionary trees ( Wu, 2018 ). Of course, sampling bias may also lead to phylogenetic errors, and increasing the sampling size can effectively improve the overall phylogenetic accuracy ( Murphy et al., 2001 ; Zwickl and Hillis, 2002 ; Dong et al., 2022a ). Although the results are different, it has been recognized that the cp genome can well analyze the phylogeny of Lauraceae, and the whole cp genome is more effective than the fragment ( Tian et al., 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…ined., proposed to conserve the name Eriobotrya against Rhaphiolepis for maintaining nomenclatural stability for this important species. Interestingly, subsequent studies by Dong et al (2022b) supported the monophyly of Eriobotrya and its separation from Rhaphiolepis using nrDNA and ITS data with larger-scale sampling. Apparently, the strongly supported but conflicting relationships were caused by the cytonuclear discordance, and the phylogenetic instability has led to conflicting treatments of Eriobotrya.…”
Section: Infrafamilial or Lower Taxonomic Scale Examplesmentioning
confidence: 96%